Assessment of Adherence to Clinical Protocols and Interface with Antimicrobial Stewardship Program - Macedo, Cibele Caspari de; Carneiro, Marcelo; Krummenauer, Eliane Carlosso; Menezes, Rochele Mosmann (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: Antimicrobial resistance is a global concern. Antimicrobial Stewardship Program interventions are necessary to guide the implementation of treatment protocols for major infectious syndromes. Aim: To evaluate the adherence rate to clinical protocols related to the prescription of antimicrobials in a teaching hospital in Rio Grande do Sul. Outlining: Retrospective cross-sectional study, conducted with secondary data from antimicrobial prescriptions of patients hospitalized in clinical units from July to December 2020. Results: 4028 antimicrobial prescriptions were evaluated, with 42.9% non-adherence to institutional clinical protocols, 39.3% with complete adherence and 17.8% with partial adherence. Implications: Knowing the adherence data to clinical protocols provides an opportunity to intervene in improvements in antimicrobial prescribing, verifying the need for permanent education for prescribers, medical students, and residents. This contributes to the promotion of rational use of antimicrobials and helps in the fight against antimicrobial resistance.